2017
DOI: 10.12688/f1000research.10969.1
|View full text |Cite
|
Sign up to set email alerts
|

A short review on the potential of coffee husk gasification for sustainable energy in Uganda

Abstract: Agricultural biomass is widely recognized as a clean and renewable energy source, with increasing potential to replace conventional fossil fuels in the energy market. Uganda, like other developing countries, has a high dependency (91%) on wood fuel, leading to environmental degradation. With a coffee production of 233 Metric Tonnes per annum, relating to 46.6 Mega Tonnes of coffee husks from processing, transforming these husks into syngas through gasification can contribute to resolving the existing energy ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In Kenya, coffee production provides a substantial income to farmers and foreign exchange to the government that is essential to improving living standards through increased GDP, tax generation, and job creation. Miito and Banadda [4] reported that only 2.5 percent of the coffee produced in the country is locally consumed despite the high tourist potential that should promote coffee value addition. Chuka's annual coffee production is about 600 kg per hectare which is lower as compared to potential production of 2,300 kg per hectare in other parts of world.…”
Section: Introductionmentioning
confidence: 99%
“…In Kenya, coffee production provides a substantial income to farmers and foreign exchange to the government that is essential to improving living standards through increased GDP, tax generation, and job creation. Miito and Banadda [4] reported that only 2.5 percent of the coffee produced in the country is locally consumed despite the high tourist potential that should promote coffee value addition. Chuka's annual coffee production is about 600 kg per hectare which is lower as compared to potential production of 2,300 kg per hectare in other parts of world.…”
Section: Introductionmentioning
confidence: 99%
“…Several application approaches are studied for low cherry husks area unit re-utilization, as a substrate for biogas [24], [25]and alcohol production [16] biosorbents for cyanide [26], biosorbents for removal of signi cant metals from liquid solutions [27], biosorbents for the removal of dyes from aqueous solutions [16] [28], biosorbents for de uoridation of water [29], biosorbentsfor lead (II) [30], for getting ready activity material converts into fuel pellets or extracted for bioactive substances recovery [16], in Ethiopia, this coffee generated enormously annually from coffee processing, but it is not utilized as its availabilities. Besides, coffee husks demonstrated to be suitable candidates for a more direct utilize as substrate for edible mushrooms production [31] or compositing [32] [33] [34]preparation of briquettes [35], bio-ethanol [36] vinegar production [37] biogas production [38] production of particleboard. Low husks are used as a possible purposeful ingredient in food production (utilizing the bottom low husk as food supplementary for usage in smoothies, granolas, and juice).…”
Section: Methodsmentioning
confidence: 99%
“…Uganda is an energy starved country despite the abundance of energy resources. The access to electricity is limited due to low income per capita, so an average household can barely afford to purchase electricity to use; as such they heavily rely of fire wood, which in turn brings environmental hazards [9]. This has often resulted into over deforestation, soil erosion and increased climate variability through reduced precipitation and longer drought periods.…”
Section: Bioenergy Resources and Sustainable Developmentmentioning
confidence: 99%